Konversi Pada Bank Perkreditan Rakyat (BPR) Menjadi Bank Perkreditan Rakyat Syariah (BPRS) dan Pengaruh Terhadap Kinerja Keuangan Pada PT. BPR Jam Gadang - Diana Purnama Sari; Anne Putri; Anwar Sholihin (ITB AAS INDONESIA Surakarta, 2023)
The Sharia law can work in Indonesia because the Indonesian banking system still adheres to a 2 window system. According to Law No. 21 of 2008 concerning Sharia banking, the 2 window banking principle in Indonesia will end no later than 2023, whereby banks that have been running Sharia business using the Sharia law will be forced to spin off or convert. One of the reasons for the conversion of Conventional Banks into Islamic Banks is the large number of Islamic financial institutions which show enormous potential, as shown by the number of Conventional Banks which have formed sharia divisions. The Islamic banking industry also applies principles that comply with Islamic law and Sharia recommendations. This study aims to see how the Conversion of Rural Banks (BPR) to Sharia Rural Banks (BPRS) and the Effect on the Financial Performance of Jam Gadang. This study uses a qualitative method with a case study approach. With the researcher can get a complete picture of the problems that are formulated by focusing on the process and the search for meaning behind the phenomena that arise in the research process. The method that can be used for this time series analysis is the Least Square Method of linear line equations from time series analysis.